Взаємодія феритового резонатора зі смужковою лінією передачі - Стоколос, М.О. (Моделювання та інформаційні технології, 2011)
The calculation theory of transmission line characteristics under the ferrite
resonator interaction is considered. It is offered to use the approached magnetic field distribution. Calculations, modelling and experimental characteristics results are spent.